Response Code Indonesian Standard (QRIS) As A Non-Cash Payment Instrument An Islamic Economic Perspective - Viona Dwi Cahyaningrum; Mila Fursiana Salma Musfiroh; Titik Hinawati (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
Purpose - This study aims to analyze the use of QRIS as a non-cash payment tool at Pakulinan Central Culinary Taman Ainun Habibie Wonosobo, based on the Islamic economic perspective of DSN MUI Fatwa Number 116/DSN-MUI/IX/2017. Methodology – The research method uses a qualitative descriptive method with a phenomenological approach, meaning that this research is focused on exploring, understanding and interpreting the meaning of phenomena, events and their relationship with ordinary people in certain situations. The data was collected using interviews and documentation, then analyzed using the Miles Huberman method. Findings - The results of the study show that the use of QRIS in Pakulinan Central Culinary Taman Ainun Habibie, almost all of them are in accordance with the Fatwa DSN MUI Number 116/DSN-MUI/IX/2017, namely regarding transactions in which riba, gharar, maysir, tadlis, and goods traded do not have haram elements. Only in one of the conditions is there something that has not been met, namely related to the storage of money that has not been carried out in Sharia banks. Implications - This study uses data from QRIS user traders at Pakulinan Central Culinary, Taman Ainun Habibie, Wonosobo.